Wildlife species distribution modeling with unmanned aircraft (Innovation & Development in Engineering and Applied Science, 2026)
Aquí tienes el texto con la ortografía y el estilo académico pulidos (no cambié el significado, solo mejoré fluidez y correcciones menores):The use of drones and open-source software in Species Distribution Models (SDMs) represents an innovative approach to the study of wildlife. This article reviews the current state of the art regarding their integration, identifying trends, challenges, and opportunities.The methodology followed the PRISMA guidelines and included a literature search in databases such as Scopus, Web of Science, and Google Scholar. Articles published within the last decade were selected if they addressed the use of drones in wildlife monitoring and the application of open-source tools in spatial data analysis.The results show a significant increase in the use of drones to collect precise geospatial data, improving the identification of habitats and species distribution patterns. Tools such as QGIS, R, and MaxEnt enable data processing without licensing costs, promoting accessibility and scientific reproducibility.However, challenges remain in terms of methodological standardization, the integration of heterogeneous data sources, and limited detection capabilities for certain species. Variability in image quality and environmental conditions also affects the accuracy of the results.In conclusion, the combination of drones and open-source software offers clear benefits: it enhances efficiency, improves model accuracy, and reduces costs. Nevertheless, greater standardization and technical validation are required to optimize its application in ecology and conservation.
Keywords: Drones; unmanned aerial vehicle (UAV); topography; accuracy; resolution; ecological reserve; protected forest; distribution model; geospatial analysis; wildlife monitoring